Vocal repertoire of Ololygon pombali (Lourenço, Carvalho, Baêta, Pezzuti & Leite, 2013) (Anura: Hylidae) from its type locality, with notes on phenotypic variation - Bang, Davi Lee; Giaretta, Ariovaldo Antonio (Zootaxa, 2018)
A recent nomenclatural change based on molecular data (Duellman et al. 2016) resurrected genus Ololygon to accommodate all taxa in the former Scinax catharinae clade (Faivovich 2002; Faivovich et al. 2005). Most Ololygon species inhabit Coastal Atlantic rainforests in northeastern and southeastern Brazil (Duellman et al. 2016), but some species occur in the Cerrado Domain (Cardoso & Haddad 1982; Pombal et al. 2010; Lourenço et al. 2013). Ololygon pombali (Lourenço, Carvalho, Baêta, Pezzuti & Leite, 2013) is a small species only known from the southern portion of Parque Nacional da Serra da Canastra, in the municipality of Capitólio, state of Minas Gerais, southeastern Brazil. Here, we describe the vocal repertoire of Ololygon pombali and provide notes on dorsal color pattern variation, while briefly discussing their taxonomic implications.